Answers

2014-09-06T16:29:29+05:30
For last question answer 3x( x + 5 ) + x ( x +6) = 2 ( x +5)  (x +6)
3x^2  + 15x + x ^2 + 6x  = 2x + 10  (x +6) 
(3 + 1) x ^2 + (15 + 6 )x = 2x^2 + 12x + 10x + 60
4x^2 + 21x = 2x^2 + 22x + 60
(4-2) x^2 + (21 -22)x - 60
2x^2 -x - 60 
1 1 1
(x^2 + 6x -x -6) - (x^2 -3x -2x +6) = x^2 +5x -6 - x^2 +5x -6 = 10x -12 = 0, 10x = 12, x = 12/10, x = 6/5 ( second question answer) , Q1 is not clear
in question 1 its' given that (x+5)whole square multiplied by(x+2)whole square which is equal to -2
(x -5) ^2 can be = x ^2 + 25 -10x and (x +2 ) ^2 can be written as x ^2 + 4 + 4x , when we multiply this we get x ^4 + 4x ^3 + 4x^2 +25x ^2 + 100 +100x -10x^2 -40x -40x^2 = -2 , then we get the answer as x^4 + 4x^3 -39x^2 + 60x + 102
is it ok friend
2014-09-06T16:46:29+05:30
 (x-5)^{2} (x+2)^{2} = -2
(x-1)(x+6)-(x-2)(x-3)=3
1 5 1